Zinc Supplementation Mitigates High Salt Diet-Induced Bone Damage: A Histological Evaluation of Osteocyte Apoptosis: Protective Effects of Zinc Against Salt-Induced Osteocyte Apoptosis: A Histological Study - Anjum , Kaukab; Qamar, Abdullah; Mahmood, Nomana; Khan, Muhammad Marghoob; Imran, Shazia; Ali, Ayesha (Journal of Rawalpindi Medical College, 2025)
Objective: This study aims to evaluate the protective role of zinc supplementation against bone damage induced by a high-salt diet, with a specific focus on osteocyte apoptosis in rats. Methods: This was an investigational study conducted at the Army Medical College, Rawalpindi, Pakistan, over eight weeks. Thirty female Sprague-Dawley rats were randomly divided into three groups: control (Group C), high-salt diet (Group A), and high-salt diet with zinc supplementation (Group B). Group C received a standard diet, Group A received a diet with 8% sodium chloride, and Group B received the high-salt diet plus zinc supplementation at 50 mg/kg body weight daily via oral gavage. After eight weeks, femurs were harvested, processed, and stained with hematoxylin and eosin. Osteocyte apoptosis was assessed by counting empty lacunae and apoptotic bodies under light microscopy. Results: The high-salt diet group (Group A) exhibited a significantly higher density of apoptotic osteocytes compared to the control group (mean ± SD: 2.3166 ± 0.820 vs. 1.3666 ± 0.431 per unit area; p=0.0005). Zinc supplementation in Group B resulted in a significant reduction in osteocyte apoptosis compared to both the high-salt diet group (mean ± SD: 1.7000 ± 0.492 per unit area; p=0.0087) and the control group (p=0.0009). These findings indicate that zinc supplementation effectively reduces osteocyte apoptosis caused by high salt intake. Conclusion: Zinc supplementation significantly mitigates the harmful effects of a high-salt diet on bone health by reducing osteocyte apoptosis. This suggests its potential as a therapeutic intervention to counteract salt-induced bone damage and prevent related diseases such as osteoporosis. Keywords: Zinc, salt, osteocytes, apoptosis, osteoporosis.